Occurrence of Diseases in Floricultural Crops in and around Jorhat, Assam - Munmi Borah; Moyurtrishna Rajkhowa; Sakendar Ali (International Journal of Economic Plants)
The objective of this study was to identify pathogenic diseases of economically important floricultural crops based on visual inspection and microscopic observation carried out during 2017-18 in and around Jorhat district of Assam. During the investigation, 3 diseases of chrysanthemum (2 fungal, 1 viral); 3 diseases of gladiolus (all fungal); 5 diseases of gerbera (all fungal), 2 diseases of rose (all fungal) and a fungal disease of marigold was identified. The diseases identified in chrysanthemum were alternaria leaf spot, sooty mould and mosaic disease. The diseases identified in Gladiolus were fusarium infection, alternaria leaf spot, curvularia leaf spot and corm rot. The diseases identified in gerbera were alternaria leaf spot, cercospora leaf spot, damping off, stemphylium infection and coniothyrium infection. Diseases identified in rose were alternaria leaf spot and cercospora leaf spot. In marigold, alternaria leaf spot was indentified causing infection to the crop. Overall pathogenic disease incidence of flower crops recorded as 60.41% in Chrysanthemum, 45.83% in Gladiolus, 55.55% in gerbera, 47.22% in rose and 45.83% in marigold. Area wise  maximum disease incidence (61.11%) was observed in Borbheta area followed by Bahona( 58.33%). Lowest disease incidence was recorded in Sungi (27.77%) in Jorhat district.